Requirement Analysis of mHealth Design in Antenatal Services at Community Health Centers in Jakarta: A Qualitative Study - Delmaifanis Delmaifanis; Kemal Nazarudin Siregar; Ryza Jazid Baharuddin Nur (Women, Midwives and Midwifery, 2023)
Background: The increased coverage of antenatal care has not matched the reduction in maternal mortality. One reason is that the antenatal care received by pregnant women is not up to standard. Following technological developments, WHO has presented a digital health intervention framework to improve the quality of antenatal care. Purpose: This Study aimed to analyze the need for mHealth development for pregnant women and health workers to provide quality ANC services. Methods: This study uses qualitative research methods, in the form of 2 Focus Group Discussions, namely for groups of service officers and pregnant women. Then 2 in-depth interviews for MCH management officers at the Health Centers and the Health Office, as well as a study of documents on recording and reporting. Data analysis was carried out thematically. The research location is in Cengkareng District, West Jakarta. Results: The main theme found was the opportunity to use mHealth in ANC services at the Health centers. pregnant women need faster service, service officers need convenience in administrative tasks. The need to remove obstacles in the form of low levels of information technology literacy, limited mobile phone memory, and lack of funds for maintaining the use of information technology. The most desirable feature of mHealth is that it can simplify the administrative tasks of service personnel and can automatically display health promotions according to the needs of pregnant women. Conclusion: there is a need to develop mHealth for pregnant women and ANC service workers equipped with features that can improve the quality of ANC services.